2020
DOI: 10.1021/acsomega.0c04449
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Release Kinetics, Equilibrium, and Thermodynamic Studies of Hymexazol onto Diatomite

Abstract: Pesticide sustained-release agents have advantages of low toxicity, high efficiency, and long duration. However, the sustained-release effects were not ideal, such as short release time and low release rate. The physical and chemical properties of diatomite are high stability, high porosity, and good sustainedrelease and controlled-release abilities. A series of diatomite-based pesticide sustained-release agents were prepared by adsorbing hymexazol onto diatomite. Kinetics, equilibrium, and thermodynamic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…For instance, equilibrating the gels at pH 3 for a few hours results in the quantitative exchange of the complex solution with water, while the process occurs overnight at pH 6. This makes the new pHEMA/PAA SIPNs appealing to a wide range of application, even beyond Cultural Heritage preservation, where controlled uptake and/or release of molecules is needed (e.g., drug delivery, wastewater treatment, agricultural industry, and food chemistry) …”
Section: Resultsmentioning
confidence: 99%
“…For instance, equilibrating the gels at pH 3 for a few hours results in the quantitative exchange of the complex solution with water, while the process occurs overnight at pH 6. This makes the new pHEMA/PAA SIPNs appealing to a wide range of application, even beyond Cultural Heritage preservation, where controlled uptake and/or release of molecules is needed (e.g., drug delivery, wastewater treatment, agricultural industry, and food chemistry) …”
Section: Resultsmentioning
confidence: 99%
“…The control of drug release by nanosized carriers, e.g., microemulsions, vesicular carriers, nanosuspensions, and wet media milling technology, also has a great impact on minimizing systemic absorption and decreasing toxicity, as in medicine and agriculture [ 74 ]. Recently, Liu et al [ 75 ] reported that modified diatomite was a highly efficient and stable carrier of hymexazol to prepare pesticide sustained-release agents suitable for neutral and acidic soil environments. Finally, possibly deleterious effects on the environment by the extensive use of combinations of active agents should be ruled out by appropriate toxicity studies [ 26 ].…”
Section: Proposed Activity Mechanisms and Future Perspectivesmentioning
confidence: 99%
“…In addition, the performance of granules can be affected by the filler. Attapulgite, kaolin, diatomite, and other inorganic minerals have a large specific surface area, strong adsorption, and good adhesion and have become important carriers in the pesticide industry. , With the development of nanocomposites, the release process can be controlled by the addition of nano-carriers, which can significantly increase pesticide coverage and effectively reduce rainwater erosion . In addition, nanoscale photothermal materials have been used to achieve physical contact with killing pests, effectively reducing the use of chemical pesticides .…”
Section: Introductionmentioning
confidence: 99%